Sustainable and efficient oil-water separation using bio tin oxide-based superhydrophobic membrane - Beagan, A.; Lin, Junyi; Lu, Yi; Mohamed, M. E. (Frontiers in Water, 2024)
Superhydrophobic materials are considered an ideal method for oil-water separation.However, existing oil-water separation methods have the problem of manufacturing complex and toxic chemical reagents. To address the limitation, we proposed a novel approach to sustainable and efficient oil-water separation using a superhydrophobic membrane based on the Bio Tin oxide nanoparticles (Bio-SnO2 NPs) synthesized from the sunflower leaf extract which was natural and non-toxic. The textile fabric was modified with a superhydrophobic coating (S.T.F), demonstrating enhanced wettability, oil absorption capacity, and oil-water separation performance. The Bio-SnO2 NPs exhibited crystalline structures with a length of 90 nm and a diameter of 20 nm, as confirmed by SEM analysis. FTIR results revealed characteristic peaks at 3410 cm -1 and 642 cm -1 , indicating the presence of hydroxyl group and Sn-O bonds confirming the successful synthesis of Bio-SnO2 NPs. BET analysis showed a substantial specific surface area of 413 m 2 /g and a pore volume of 0.19 cm 3 /g, emphasizing the textural properties. The FTIR and SEM techniques were used to study the characteristics of the textile fabric before and after modification with the superhydrophobic coat. The S.T.F exhibited remarkable superhydrophobicity with a water contact angle of 152° and a water sliding angle of 4°. Absorption capacities for coconut oil, diesel, and hexane were found to be 70.4 g/g, 63.5 g/g, and 49.6 g/g, respectively, with excellent cyclic stability.Separation efficiency for hexane, diesel, and coconut oil was found to be 99.5, 97.1%, and 96.3%, respectively, with excellent cyclic stability. Mechanical stability test revealed superhydrophobicity retention even after an abrasion length of 200 mm. The chemical stability test indicated that the superhydrophobicity was maintained in the pH range of 3-11. Moreover, the flux for hexane, diesel, and coconut oil was 9400 L m -2 h -1 , 8800 L m -2 h -1 , and 8100 L m -2 h -1 , respectively, highlighting the membrane's efficient oil-water separation capabilities. These results collectively position the developed S.T.F as a promising and sustainable solution for diverse oil-water separation applications.